ERAmerica records - ERAmerica (Organization)
Correspondence, memoranda, minutes, bylaws, speeches, subject files, press files, state files, organization files, bibliographies, petitions, legal files, financial records, card files, photographs, and other records relating to the Equal Rights Amendment. Individuals represented include Liz Carpenter, Suone Cotner, and Elly Maude Peterson.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
A nationwide alliance of civic, labor, church, and women's organizations founded in 1976 to promote ratification of the amendment that had passed Congress in 1972.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carpenter, Liz; Cotner, Suone; Peterson, Elly Maude, -- 1914-2008.; United States; Constitutional amendments -- United States; Equal rights amendments -- United States; Sex discrimination -- United States